2007
DOI: 10.1519/r-17435.1
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Activity of the Trunk Stabilizers During Stable and Unstable Bench Press

Abstract: The purpose of this study was to investigate the effectiveness of instability training in the recruitment of core stabilizing muscles during dynamic multijoint movement. Surface electromyography (EMG) was measured from 6 muscles (latissimus dorsi, rectus abdominus, internal obliques, erector spinae, and soleus) while subjects performed a 9.1-kg bench press on stable and unstable surfaces. There were 4 exercises in total: (a) stable surfaces for shoulders and feet, (b) upper-body instability, (c) lower-body ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 0 publications
2
66
0
4
Order By: Relevance
“…4,5 The use of unstable surfaces has increased in popularity when prescribing exercises for core stability training. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Free weight exercises that were previously performed on stable ground and benches are now commonly performed on unstable surfaces. For example, the squat is now commonly performed while standing on balance discs and the overhead press is now commonly performed while seated on a stability ball.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The use of unstable surfaces has increased in popularity when prescribing exercises for core stability training. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Free weight exercises that were previously performed on stable ground and benches are now commonly performed on unstable surfaces. For example, the squat is now commonly performed while standing on balance discs and the overhead press is now commonly performed while seated on a stability ball.…”
mentioning
confidence: 99%
“…6,7,9,11,15 Previous research has demonstrated greater activation in the core muscles when free weight lifts were performed on unstable surfaces. 6,7,16 Anderson and Behm 6 compared core muscle activity (eg, abdominal stabilizers, upper lumbar erector spinae, lumbosacral erector spinae) during three squat lifts with varying levels of instability: (1) an unstable squat performed while standing on balance discs, (2) a stable squat performed with a free weight bar while standing on stable ground, and (3) a very stable squat performed in a Smith machine while standing on stable ground. The authors demonstrated that the activity of all muscles examined increased progressively from the very stable to the unstable squat.…”
mentioning
confidence: 99%
“…17,22 The wall press and bench press are CKC exercises that elicit activity from the upper extremity muscles and are frequently used in rehabilitation protocols, 18,27,28,32 as well as in recreational and professional athletic performance training. 11,27,31,34,36 Nevertheless, due to limited information regarding muscle demand and load applied onto the shoulder, the phase of a rehabilitation program in which these exercises should be introduced remains unclear. 38,41 The purpose of this study was to quantify muscle activity elicited during isometric wall press and isometric bench press tasks in 7 muscles shown in the literature to be important for shoulder movement.…”
Section: T T Resultsmentioning
confidence: 99%
“…Among them, there are general reports on the impact of technological facilities on the result [1], detailed papers regarding the structural dimensions of the competitors' bodies [2], as well as comments about the essence of stretching [3], vibration exercise [4], or sports performance. Studies concerning techniques in PL [5] and the values of selected muscle bio-potentials during their implementation [6] are particularly interesting.…”
Section: Introductionmentioning
confidence: 99%